Geochemical controls and characteristics of natural seepage of carbon dioxide along the Bongwana Fault, KwaZulu-Natal and Eastern Cape Provinces - Sello, Jabulani Justice (My University, 2019)
This study was intended to investigate the major geochemical processes controlling the aqueous CO2 detected in selected sampling points along the Bongwana Fault, considering the characteristics and potential impacts thereof. Various complementary methods were used to identify the major geochemical processes governing the chemical compositions of the waters in the study area. These include isotope analysis, classification of water facies, stoichiometric and bivariate analysis for water-rock interactions assessment and geochemical modelling (determination of mineral Saturation Indices). The δ18O and δ2H isotopes indicated that there is mixing of connate and recently recharged waters in the groundwater system. However, poor construction of Bongwana boreholes overemphasises the rate of recharge in the sampling area as the boreholes allow rainwater to percolate and dilute the preserved compositions during periods of heavy rainfall. The source of CO2 in the area was investigated using δ13C and results revealed the source to be carbonate dissolution attributed to the reaction of acidic groundwater with the Marble Delta Formation carbonate rocks. Further analysis indicated that carbonate dissolution is coupled and interchangeable with calcite re-precipitation to form the travertines that were seen covering the surfaces in Umtamvuna and Bongwana areas as a result of CO2 degassing. Carbonate dissolution under the influence of temperature, pH, saturation states and pCO2 is the principal geochemical process controlling the observed chemical compositions as free Ca2+ and HCO3− are released in solution. Geochemical modelling indicated that calcite is oversaturated with respect to the solution it is contained in; hence more travertine will continue to form from saturated groundwater in Umtamvuna. Moreover, geochemical modelling also shows CO2 will be released without forming any travertine surfaces in Bongwana since calcite is undersaturated and is less likely to precipitate. The Msikaba Formation sandstone is the main aquifer in the study area and is influenced by connate waters of marine origin, introducing high concentrations of Na+, Cl− and SO42−. Water-rock interaction indicated that reverse ion exchange is prevalent which resulted in the exchange of Ca and Na as indicated by the following dominant water facies: Na-Mg-HCO3-Cl and Na-Mg-HCO3-Cl-SO4 driven by halite dissolution. Umtamvuna groundwater are ionically related and connected at depth through fractures.
A Research Report submitted to the Faculty of Science, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Hydrogeology, School of Geosciences, October 2019